Comparative Analysis of AES (Advanced Encryption Standard) and Blowfish Algorithms in Camera Module IoT Applications - Hidayati, Nurul; Zulaykhah, Ikrimatuz; waluyo, waluyo; Adzikirani, Adzikirani (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2025)
The development of technology is currently becoming very advanced and sophisticated which results in many data leaks by irresponsible individuals, so data security is mandatory. Data that is easily hacked is usually images sent through social media. This research aims to secure image transmission data using Telegram BOT. The selection of social media is because Telegram does not yet have encryption for data transmission security. The methods used are AES (Advanced Encryption Standard) and Blowfish because AES is the strongest algorithm today while Blowfish was once named the best and patent-free algorithm. So it is appropriate to conduct a comparative analysis on AES and Blowfish. Duration testing carried out using unequal sizes has an encryption process value of 100-200 ms consistently. For the duration description time of the smallest and largest image has the same value of 300 ms. For the same image size, the better the AES algorithm, the longer the duration of time while the Blowfish algorithm has a faster time than AES. As for the description process Blowfish Algorithm has the longest duration and AES 192 has the fastest duration